PENGARUH GAME ONLINE TERHADAP KESANTUNAN BERBAHASA SISWA DALAM INTERAKSI SOSIAL DI MI MA’ARIFUL PALEMBANG - Rekyan Abdul Halim; Maryamah; Muhamad Afandi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the increasing phenomenon of online game usage among elementary Islamic school students, which potentially affects language politeness in social interactions. The purpose of this study is to determine the intensity level and types of online games played by students, describe the forms of students' language politeness in social interactions, and analyze the influence of online gaming on students' language politeness at MI Ma'ariful Ulum Palembang. The method used is a quantitative method with a simple linear regression approach. Data collection techniques were carried out by distributing questionnaires to 125 respondents selected using simple random sampling technique. The research instrument consisted of 50 Likert-scale statements that had been tested for validity and reliability. Data analysis was performed using IBM SPSS version 26 through validity tests, reliability tests, normality tests, linearity tests, simple linear regression analysis, t-tests, F-tests, and coefficient of determination. The results showed that the intensity level of students' online gaming was in the moderately intensive category with a mean score of 79.00, dominated by MOBA and FPS type games. Students' language politeness was generally in the polite category with a mean score of 93.39. Based on the regression analysis, the equation Y = 28.440 – 0.191X was obtained with a t-value of -3.839 and a significance of 0.000 < 0.05, proving that online games have a negative and significant effect on students' language politeness. The coefficient of determination (R²) of 0.202 indicates that online games contribute 20.2% to the variation in students' language politeness, while the remaining 79.8% is influenced by other factors outside this study.